BAHASA JARGON PADA KOMUNITAS REMAJA DI SITUBONDO (Analisis Diskripsi Kualitatif Penggunaan Bahasa Jargon Pada Komunitas Remaja Di Situbondo) - Aenor Rofek (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
Jargon in a community that aims to create an exclusive language or languages understood by the group and as a manifestation of the existence of a group. It is so interesting to watch, so that all beings are contained in the jargon of the teen community in the town of Situbondo. Jargon contained in the teen community is very varied and this is great for our results. The forms of the jargon used in the teen community in Situbondo, including the form and characteristics jargon jargon. A form of jargon include (1) the form of the lexicon consists of a basic word, affix, abbreviations and acronyms; The characteristics of jargon include (1) jargon is internal, (2) jargon serves to identify themselves, (3) jargon such as shortening of the word